We Are What We Eat In A House for Mr Biswas and the Inheritance of Loss - Saher, Najma; Sadaf, Shazia (The Journal of Humanities & Social Sciences, 2022)
In The Inheritance of Loss and A House for Mr. Biswas, food might be recognized as an all-important metaphor for self-identification. Food is loaded with meaning about relations, communion, home and identity. In the said texts, food becomes a powerful voice for an emptiness which lives on as a physical craving and a continual sense of discomfort. Identity seems to become physical and instinctive when it comes to food. Interestingly in the postcolonial moment, food appears to lose its capacity for gratification and either acts as a catalyst for evoking disappointment, or a metaphor for self-estrangement that is usually experienced by the displaced subject. This paper aims to show the effects of colonization on the characters’ eating habits and their struggle at dining table and around kitchen. The native is lured into preferring western food over local cuisine so as to cover his colonial inadequacy but most often get deprived of the food that has been satisfying both to his palate and his stomach.